FUNCTIONS, TYPES, AND ADVANTAGES OF LUBRICATION SYSTEMS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article examines the functions, types, and advantages of lubrication systems in modern mechanical engineering. It highlights the importance of lubrication in reducing friction, preventing wear, cooling machine components, and ensuring efficient operation. The study also describes different types of lubrication systems and analyzes their practical applications in various industries. Furthermore, the article emphasizes the economic and environmental benefits of proper lubrication.